Physical and mental health status and influencing factors of older adults in community-dwelling in Northeast China: a cross-sectional study - Gao, Mingcheng; Chen, Ziyang; Li, Jing; Liu, Yue; Lv, Run; Chen, Huanhong; Zhang, Lulu; He, Yining; Guo, Na; Zhang, Yuping; Zhang, Ying; Dai, Xin (Frontiers in Public Health, 2024)
BackgroundBetween 2020 and 2022, the COVID-19 pandemic spread globally, and the implementation of preventive measures led to reduced outdoor activities for older adults, resulting in a decline in social functioning. This study aims to improve community-based health interventions tailored to older adults experiencing physical and psychological declines following the COVID-19 pandemic.MethodsThis study utilized previous data mining results to estimate the demand for community health services for older adults. It involves collecting questionnaire responses to understand the basic characteristics and lifestyle behaviors of older adults. The severity of health issues among older adults was assessed using the KCL and GHQ-12 scales. Statistical analyses included descriptive statistics, chi-square tests, t-tests, ANOVA, non-parametric tests as applicable, and stratified binary logistic regression to determine the factors influencing the health status of older adults.ResultsOver 60% of the older adult population suffers from chronic diseases, and more than 70% do not participate in social activities. In the overall older adults, the detection rate for poor health is 15.60%. Chronic illness, reduced ability to perform daily activities, anxiety, poor self-rated health, sleep disturbances, and nutritional imbalance were identified as key risk factors affecting the health of older adults in the community.ConclusionOlder adults mainly engage in physical exercise, maintain a healthy lifestyle, and control their diet as self-care strategies. Early signs of frailty are characterized by declines in lower limb muscle function and memory. The most common manifestation of poor health among older adults is anxiety.